Interplay between purinergic signalling and extracellular vesicles in health and disease - Carotti, Valentina; Rigalli, Juan Pablo; van Asbeck-van der Wijst, Jenny; Hoenderop, Justinus Gerardus Johannes (Biochemical pharmacology, 2022)
Purinergic signalling is a receptor-mediated process characterized by the binding of extracellular nucleotides and nucleosides to purinergic receptors, which results in the activation intracellular signalling pathways, and, ultimately, leads to changes in cell physiology. Purinergic signalling has been related to the regulation of important physiological processes (e.g., renal electrolyte reabsorption; platelet aggregation; immune response). In addition, it has been associated with pathophysiological situations such as cancer and inflammation. Extracellular vesicles (EVs) are nanoparticles released by all cells of the organism, which play a key role in cell-cell communication. In this regard, EVs can mediate effects on target cells located at distant locations. Within their cargo, EVs contain molecules with the potential to affect purinergic signalling at the target cells and tissues. Here, we review the studies addressing the regulation of purinergic signalling by EVs based on the cell type or tissue where the regulation takes place. In this regard, EVs are found to play a major role in modulating the extracellular ATP levels and, specially, adenosine. This has a clear impact on, for instance, the inflammatory and immune response against cancer cells. Furthermore, we discuss the data available on the regulation of EV secretion and its cargo by purinergic signalling. Here, a major role of the purinergic receptor P2X7 and again, an impact on processes such as inflammation, immune response and cancer pathogenesis has been established. Finally, we highlight uninvestigated aspects of these two regulatory networks and address their potential as therapeutic targets.